Effect of CNC Ball Nose End Milling Process Parameters on Surface Roughness and Chip Length of Aluminium Alloy 6061 - Hussein, Nur Izan Syahriah; Md Ali, Mohd Amran; Sivarao, Subramonian (Universiti Teknikal Malaysia Melaka, 2012)
This paper reports the effect of process parameters on surface roughness of Aluminum Alloy 6061 after being machined with CNC ball nose end milling process. The cutter was made of high speed steel. The studied parameters were spindle speed, feed rate and depth of cut. The results showed that depth of cut gave major influence to the surface roughness. The increased in cutting depth also resulted in increased of chip length. By using Taguchi Method and ANOVA analysis, the experimental data were analyzed and discussed. Findings from this study contribute to further understanding of the machinability of Aluminium Alloy 6061, in which widely used for transportation and machinery components.